PRICIPLES OF ECONOMIC SECURITY OF THE EURASIAN ECONOMIC UNION - Sh. M. Omarov (Финансы: теория и практика)
As is well-known, by 2015 Russia, Kazakhstan and Belarus are planning to form the Eurasian Economic Union (EAEU) on the basis of the already established Customs Union (CU) and Common Economic Space (CES). Therefore, the economic security of the Eurasian integration process has to be studied and analyzed to ensure long-term sustainability and development. Given the economic and financial problems faced by the European Union, this study is becoming particularly relevant. The article substantiates the importance of creating effective mechanisms to enhance the economic stability of the EAEU and its ability to withstand periodic crises arising in the global economy with shrinking intervals. The research findings may be used by both national government authorities of the CU and the EUS and a supernational body - the Eurasian Economic Commission.